Identification of patients with low risk of severity in confirmed COVID-19 cases. Cuba, 2020- 2021 - Maicel Eugenio Monzón-Pérez; Lizet Sánchez-Valdés; Agustín Lage-Dávila (Revista Habanera de Ciencias Médicas)
Introduction: The COVID-19 pandemic, a treat to global health, overwhelmed health systems in many countries. Performing and adequate identification of subjects with very low risk to develop a severe form of the disease is of vital importance.